2020
DOI: 10.3390/ijms21031144
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-6 Knockout in the 5xFAD Model of Alzheimer’s Disease Reveals Favorable Outcome on Memory and Neurological Hallmarks

Abstract: Alzheimer's disease (AD) is a progressive neurodegenerative disorder and is the most common form of dementia in the elderly. Caspases, a family of cysteine proteases, are major mediators of apoptosis and inflammation. Caspase-6 is considered to be an up-stream modulator of AD pathogenesis as active caspase-6 is abundant in neuropil threads, neuritic plaques, and neurofibrillary tangles of AD brains. In order to further elucidate the role of caspase-6 activity in the pathogenesis of AD, we produced a double tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 82 publications
4
16
0
Order By: Relevance
“…Sequentially, they aggravate the damage of microglia and form negative feedback regulation to advance the course of the disease 62,70 . For example, increased levels of IL‐1β promote abnormal neuronal and synaptic dysfunction, giving rise to impaired memory 71 . EPA and DHA are conditionally essential fatty acids that are inefficiently synthesized by human body.…”
Section: Discussionmentioning
confidence: 99%
“…Sequentially, they aggravate the damage of microglia and form negative feedback regulation to advance the course of the disease 62,70 . For example, increased levels of IL‐1β promote abnormal neuronal and synaptic dysfunction, giving rise to impaired memory 71 . EPA and DHA are conditionally essential fatty acids that are inefficiently synthesized by human body.…”
Section: Discussionmentioning
confidence: 99%
“…However, when defined by electroencephalography recordings there are seizures in 5xFAD mice, possibly as early as 4 months ( Abe et al, 2020 ), but that become prevalent at older ages (>10 months) ( Paesler et al, 2015 ; Abe et al, 2020 ; Angel et al, 2020 ). In addition, one proposal is that the abnormal epileptiform activity predisposes 5xFAD mice to convulsive seizures with further stress, as has been demonstrated with genetic approaches ( Paesler et al, 2015 ; Angel et al, 2020 ). Our data that 0% of E3FAD+ mice experience seizures are consistent with these findings, however, E4FAD+ mice did undergo a tonic-clonic seizures.…”
Section: Discussionmentioning
confidence: 99%
“…For example, caspase-6 (CASP6) plays a key role in pyroptosis.As a member of caspase family, CASP6 is categorized as an executioner but shows some differences the other executioners, aberrantly activated at the early stage of AD [12] . Studies have shown that high expression of CASP6 is related to anxiety behavior and worse memory in AD mice [13] .…”
Section: Introductionmentioning
confidence: 99%